Parental phenotype not predator cues influence egg warning coloration and defence levels. (June 2018) - Paul, Sarah Catherine; Stevens, Martin; Pell, Judith K.; Birkett, Michael A.; Blount, Jonathan D.
Abstract : In species that advertise their toxicity to predators through visual signals, there is considerable variation among individuals in both signal appearance and levels of defence. Parental effects, a type of nongenetic inheritance, may play a key role in creating and maintaining this within-species diversity in aposematic signals; however, a comprehensive test of this notion is lacking. Using the ladybird Adalia bipunctata, we assessed how egg coloration and defence level (concentration of the toxic alkaloid (-)-adaline) is influenced both by simulated predation risk in the egg-laying environment and by parental phenotype (coloration and toxin level). We found that egg toxin level and colour were predicted by parental phenotype but were not altered in response to cues of egg predators. Egg luminance (lightness) was positively correlated with paternal elytral luminance, while maternal toxin level positively predicted egg toxin level. In response to egg predator cues, ladybird mothers altered the timing of laying and total egg number, but not egg toxin level or colour. It appears therefore that in A. bipunctata variation between individuals of the same morph in the colour and toxin level of the eggs they lay, that is, egg aposematic phenotype, is more strongly influenced by individual variation in parental aposematic traits than by environmental cues of egg predation risk. Furthermore, these results provide the first indication that, in a warningly coloured species, male coloration may play a dual role as predator deterrent and indicator of paternal quality, influencing maternal investment in offspring. Highlights: Parental effects may impact within-species diversity in aposematic signals. How parental effects influence egg phenotype in aposematic species is investigated. Egg toxin level and colour were predicted by parental phenotype not predation risk. Male coloration may also influence maternal investment in offspring.